The Role of School and Vocational Guidance Counselor in Reducing School Bullying, from the Point of View of Middle Education Teachers - Djeffal, Meriem (جامعة زيان عاشور الجلفة, 2021)
تهدف الدراسة لمعرفة دور مستشار التوجيه والإرشاد المدرسي والمهني في التقليل من التنمر المدرسي من وجهة نظر أساتذة التعليم المتوسط، وأجريت على عينة قصدية من أساتذة التعليم المتوسط (124 أستاذا) بعدة مجموعات فايسبوكية خاصة بأساتذة التعليم المتوسط. حيث اعتمدت على المنهج الوصفي التحليلي، أين قدر مجتمع الدراسة ب 17 مجموعة فايسبوكية، واستخدم الاستبيان الإلكتروني كأداة للدراسة تتكون من (37 بند) موزعة على محورين: الإعلام يشمل (21 بند) "والمتابعة النفسية" ويشمل (16 بند). توصلت الدراسة إلى أن لمستشار التوجيه دور في التخفيف من التنمر المدرسي ولكن ليس بالقدر المطلوب إذ يكتفي إلا بمحور الإعلام أما المتابعة النفسية فهي قليلة نوعا ما وذلك حسب نظر أساتذة التعليم المتوسط.
The study aims to identify the school and vocational guidance counselor’s role in reducing school bullying from middle school teachers’ viewpoint It was conducted on a purposeful sample of 124 middle school teachers from study community estimated with 17 Facebook groups for intermediate education teachers. Furthermore, the descriptive and analytical approach was adopted. The electronic questionnaire was used as a study tool consisting of (37 items) divided on two axes: Information (21 items) and the Psychological follow-up (16 items) ).The study found that the school and vocational guidance counselor has a role in reducing school bullying, but not to the required extent, as s/he relies only on informing axis, where as psychological follow-up is rarely used, according to the view of middle education teachers.
Keywords: علم النفس التربوي -- التوجيه التربوي -- العنف المدرسي -- الاضطرابات السلوكية -- معلمو المرحلة المتوسطة